CONFLICT MANAGEMENT BETWEEN TEACHERS AND STUDENTS: CASE OF ESPERANTO PRIVATE HIGH SCHOOL IN MADAGASCAR - Ralaivao Hanginiaina Emynorane; Hangivola Emyblonde Ratna; Yudin Citriadin; Arrive Tsitaire Jean; Razafiharimbola Larissa (Jurnal Pendidikan (Teori dan Praktik), 2024)
This study aims to understand in depth the dynamics of management conflicts between teachers and students in school through a qualitative approach using interview techniques. This study involved teachers, students, parents and principal from Esperanto private High School in Madagascar who were selected purposively to represent a variety of perspectives. Interviews were conducted with the aim of identifying the factors that caused the conflicts and how each party proposed some solutions to manage the conflicts. The findings show that conflicts between teachers and students can appear in various forms, ranging from disagreements in teaching methods, differences in expectations between teachers and students, to student behavior problems that affect the learning process. Ineffective conflict management in school causes negative impacts, both on the learning environment and on students' emotional development. Some of the strategies found in this study include open communication, a more flexible approach from teachers, and providing space for students to actively participate in learning. With a deeper understanding of the causes and impacts of conflicts, school has to design more effective policies to address this problem, as well as improving the quality of learning to more inclusive and supporting student development.